The Arga-EL Method: A Structured Colour Breathing Framework for Attentive Respiratory Guidance toward the Eternal Light (Allah): English - Lubis, Arga Abdi Rafiud Darajat; Khairina Azni (CV. ARGA FARMA, 2026)
This article introduces the Arga-EL Method [Attentive Respiratory Guidance toward the Eternal Light (Allah)], a structured colour-breathing framework designed to integrate contemplative posture, controlled respiration, symbolic colour visualization, and intentional emotional release within a spiritually oriented practice. Drawing conceptually from historical breath traditions, selected Gateway Experience materials, and cross-traditional seated contemplative disciplines, the method proposes a practical sequence through which breathing becomes not only a physiological act but also a medium of inward regulation and luminous orientation. The protocol begins with environmental preparation and upright seated alignment, followed by focused breath regulation, numerical visualization to stabilize inner attention, and colour-guided breathing sequences. In this framework, blue is inhaled to cultivate calmness and release irritation, while white is inhaled to induce purity and inner quiet, accompanied by the symbolic exhalation of red as emotional turbulence or anger. The practice is designed to be performed in a minimum three-minute cycle and may be extended to fifteen minutes for deeper relaxation and contemplative absorption. The discussion further situates the method within broader scholarship on breath regulation, colour-emotion associations, and symbolic contemplative practice.